Ethylene vinyl acetate as a multifunctional compatibilizer for natural rubber/cis-1,4-polybutadiene rubber blends with enhanced compatibility, filler dispersion and mechanical properties - Jiyu Liang; Jianhui Wu; Chunhua Wang; Jun Sang; Keshuai Ren; To Ngai; Wei Lin (Collagen and Leather)
Abstract The blending of natural rubber (NR) with cis-1,4-polybutadiene rubber (BR) has gained widespread attention due to its potential in enhancing the low temperature resistance and abrasion resistance of NR. However, the incompatibility between NR and BR as well as the non-uniform distribution of fillers often have an adverse impact on the mechanical properties. Herein, we propose a facile approach to modulate the multi-scale structures in NR/BR blends including polymer compatibility and filler distribution by introducing ethylene vinyl acetate (EVA) with varying vinyl acetate (VA) content as multifunctional compatibilizers. The results indicate that the cure characteristics (i.e., processability) and mechanical properties of NR/BR blends can be readily tailored through adjustment of the VA content in EVA. When the VA content in EVA is increased to 18% (EVA-18), the NR/BR blends simultaneously exhibit favorable processability and mechanical properties. The microstructural analysis demonstrates that the introduction of EVA-18 not only enhances the compatibility between NR and BR with significantly reduced domain size, but also improves fillers dispersion in the rubber matrix. The presence of EVA-18 at concentrations up to 20 parts per hundred of rubber (phr) in NR/BR vulcanizates improves the mechanical properties by approximately 24% compared to un-compatibilized NR/BR vulcanizates, which is superior to the most present studies. This work will be beneficial for the development of NR/BR blends in the industry and provide a guideline for designing efficient compatibilizers for other immiscible rubber blends. Graphical abstract